Cardiomyopathy and Worsened Ischemic Heart Failure in SM22-α Cre-Mediated Neuropilin-1 Null Mice. Issue 6 (June 2015) - Wang, Ying; Cao, Ying; Yamada, Satsuki; Thirunavukkarasu, Mahesh; Nin, Veronica; Joshi, Mandip; Rishi, Muhammed T.; Bhattacharya, Santanu; Camacho-Pereira, Juliana; Sharma, Anil K.; Shameer, Khader; Kocher, Jean-Pierre A.; et al.
<x xml:space="preserve">Abstract</x> Objective— Neuropilin-1 (NRP-1) is a multidomain membrane receptor involved in angiogenesis and development of neuronal circuits, however, the role of NRP-1 in cardiovascular pathophysiology remains elusive. Approach and Results— In this study, we first observed that deletion of NRP-1 induced peroxisome proliferator–activated receptor γ coactivator 1α in cardiomyocytes and vascular smooth muscle cells, which was accompanied by dysregulated cardiac mitochondrial accumulation and induction of cardiac hypertrophy- and stress-related markers. To investigate the role of NRP-1 in vivo, we generated mice lacking Nrp-1 in cardiomyocytes and vascular smooth muscle cells (SM22-α-Nrp-1 KO), which exhibited decreased survival rates, developed cardiomyopathy, and aggravated ischemia-induced heart failure. Mechanistically, we found that NRP-1 specifically controls peroxisome proliferator–activated receptor γ coactivator 1 α and peroxisome proliferator–activated receptor γ in cardiomyocytes through crosstalk with Notch1 and Smad2 signaling pathways, respectively. Moreover, SM22-α-Nrp-1 KO mice exhibited impaired physical activities and altered metabolite levels in serum, liver, and adipose tissues, as demonstrated by global metabolic profiling analysis. Conclusions— Our findings provide new insights into the cardioprotective role of NRP-1 and its influence on global metabolism.